Hearing vulnerability after noise exposure in a mouse model of reactive oxygen species overproduction. Issue 4 (23rd July 2018) - Morioka, Shigefumi; Sakaguchi, Hirofumi; Yamaguchi, Taro; Ninoyu, Yuzuru; Mohri, Hiroaki; Nakamura, Takashi; Hisa, Yasuo; Ogita, Kiyokazu; Saito, Naoaki; Ueyama, Takehiko
Abstract: Previous studies have convincingly argued that reactive oxygen species (ROS) contribute to the development of several major types of sensorineural hearing loss, such as noise‐induced hearing loss (NIHL), drug‐induced hearing loss, and age‐related hearing loss. However, the underlying molecular mechanisms induced by ROS in these pathologies remain unclear. To resolve this issue, we established an in vivo model of ROS overproduction by generating a transgenic (TG) mouse line expressing the human NADPH oxidase 4 ( NOX4, NOX4‐ TG mice), which is a constitutively active ROS‐producing enzyme that does not require stimulation or an activator. Overproduction of ROS was detected at the cochlea of the inner ear in NOX4 ‐TG mice, but they showed normal hearing function under baseline conditions. However, they demonstrated hearing function vulnerability, especially at high‐frequency sounds, upon exposure to intense noise, which was accompanied by loss of cochlear outer hair cells (OHCs). The vulnerability to loss of hearing function and OHCs was rescued by treatment with the antioxidant Tempol. Additionally, we found increased protein levels of the heat‐shock protein 47 (HSP47) in models using HEK293 cells, including H2 O2 treatment and cells with stable and transient expression of NOX4. Furthermore, the up‐regulated levels of Hsp47 were observed in both the cochlea and heart of NOX4 ‐TG mice. Thus, antioxidant therapy is a promising approach for the treatment of NIHL. Hsp47 may be an endogenous antioxidant factor, compensating for the chronic ROS overexposure in vivo, and counteracting ROS‐related hearing loss. Abstract : Evidence for reactive oxygen species (ROS) contribution to sensorineural hearing loss is convincing; however, the underlying mechanisms remain unclear. We generated an in vivo mouse ROS overproduction model, particularly, a transgenic (TG) mouse line expressing NADPH oxidase 4 ( NOX4, NOX4‐ TG mice). The NOX4 ‐TG mice constitutively produced ROS without stimulation or an activator; however, they did not show hearing loss under baseline conditions. Nevertheless, intense noise exposure increased hearing vulnerability of NOX4 ‐TG mice; this was rescued by the antioxidant Tempol. Interestingly, Hsp47 was up‐regulated in NOX4 ‐TG cochlea, acting as a putative antioxidant.